Prototype Sistem Monitoring Intensitas Cahaya pada Budidaya Tanaman Cabai Rawit dengan Konsep Smart Farming Berbasis Internet Of Things (IOT) - Yusa, Ahmad Martin; Nurhalimah, Siti; Fahmi, Arif (Politeknik Negeri Banyuwangi Jl. Raya Jember km. 13 Labanasem, Kabat, Banyuwangi, Jawa Timur (68461) Telp. (0333) 636780, 2023)
Light intensity is an important factor to consider as best as possible to support plant fertility and health, especially in cayenne pepper plants. One of the innovations that can be applied to assist the management and maintenance of plants in Greenouse is agricultural technology based on the Internet of Things (IoT) or called smart sarming. In the use of Smart farming technology, the process of Monitoring crop needs is carried out by sensors and microcontrollers so that farmers can monitor all data in real time. This final project aims to describe the implementation of a light intensity Monitoring system in an IoT-based Greenhouse and produce a light intensity Monitoring tool in a Greenhouse using an LDR sensor so that farmers can know that the plants are getting an adequate supply of light. The smart farming system is designed using the MQTT (Message Queue Telemetry Transport) protocol as the center for transferring and receiving data from sensors to Monitoring applications. The stages of implementing system into the Greenhouse include: (1) installation of sensors and microcontrollers on the Prototype Greenhouse for cayenne pepper cultivation; (2) design and decision-making to be carried out by the system; (3) create web and android applications as a place for Monitoring data by end users. The results show that the light intensity Monitoring system in cayenne pepper cultivation is based on the Internet Of Things (IoT), include: first, the manufacture of a system Monitoring tool whose light intensity is carried out in 4 steps, namely determining the components, assembling of components into a series of Monitoring systems, programming toolkits and application software, and packaging step. And the second, the implementation of the light intensity Monitoring system in cayenne pepper cultivation includes the system trial stage which produces an average value of 2676 LUX or 62.43% on sensor readings 12 times over a period of 3 minutes it is still at the optimal level for the growth of cayenne pepper plants with a minimum intensity value of 2528 or 50%. The output value calibration results on the Monitoring application with the LUX Meter application show the same and accurate value. So, it can be concluded that the IoT-based light intensity Monitoring system can run well and can be implemented for Greenhouse farming of cayenne pepper.